Guinea : Staff Report for the 2005 Article IV Consultation and Staff-Monitored Program. (IMF Staff Country Reports; Country Report, 2006)
This 2005 Article IV Consultation highlights that Guinea's economic performance has deteriorated in recent years, largely as a result of a weak policy framework and against a background of mounting regional insecurity and low prices for its main commodity exports. Economic growth since 2000 has slowed to an average of about 2.5 percent, inflation accelerated to almost 30 percent, and international reserves fell to less than one month of imports. Real GDP growth is expected to recover moderately in 2005, but little progress is expected in reducing inflation.